Space-time adaptive processing for radar - Guerci, J. R. (Artech House radar library., 2003)
Annotation "Based on a time-tested course taught in industry, government, and academia, Space-Time Adaptive Processing for Radar introduces basic STAP concepts and methods, placing emphasis on implementation in real-world systems. This practice resource provides the analysis tools needed to assess the impact of STAP on a variety of important radar applications. The toolkit of STAP algorithms and implemention techniques included in the book allows practitioners the flexibility of adapting the best methods to their applications." "From important factors affecting STAP performance to reduced-rank and minimized sample support STAP, the book clearly explains critical topics in a manner that is easily understandable to anyone with a basic background in radar and signal processing. Moreover, this unique reference includes detailed descriptions of the latest developements in STAP research, helping professionals keep up with important trends in the industry."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved